TI_GERICHTE 52.2016.493 vom 20. Februar 2017 , Revoca della licenza di condurre a titolo preventivo e cautelativo - TI Tribunale d'appello (2017)
Revoca della licenza di condurre a titolo preventivo e cautelativo